1999
DOI: 10.3354/meps184063
|View full text |Cite
|
Sign up to set email alerts
|

Water flow in tide- and wave-dominated beds of the seagrass Thalassia testudinum

Abstract: Biological processes in seagrass meadows are regulated by the exchange of momentum, heat and mass between the surrounding water and the plants and thus may strongly depend on the characteristics of water flow and turbulence. Comparisons of mean flow profiles, turbulence distribution and mixing in meadows of the seayrass Thalassia testudinum colonizing 2 hydrodynamically different sites (wave-dominated and tide-dominated) suggest that the hydrodynamic microclimate and consequently mixing within seagrass beds st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
151
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(164 citation statements)
references
References 23 publications
5
151
1
Order By: Relevance
“…Moreover, seagrass canopies strongly enhance sedimentation by reducing current velocity and wave energy. Canopy trapping has been demonstrated in temperate areas (Koch 1999, Koch & Gust 1999, Terrados & Duarte 2000, Granata et al 2001 as well as in tropical ones (Agawin & Duarte 2002, Gacia et al 2003. In a seagrass meadow dominated by Thalassia hemprichii, Agawin & Duarte (2002) showed that particle loss is 4 times higher than in unvegetated areas, suggesting an important transfer of planktonic production to the seagrass meadow.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, seagrass canopies strongly enhance sedimentation by reducing current velocity and wave energy. Canopy trapping has been demonstrated in temperate areas (Koch 1999, Koch & Gust 1999, Terrados & Duarte 2000, Granata et al 2001 as well as in tropical ones (Agawin & Duarte 2002, Gacia et al 2003. In a seagrass meadow dominated by Thalassia hemprichii, Agawin & Duarte (2002) showed that particle loss is 4 times higher than in unvegetated areas, suggesting an important transfer of planktonic production to the seagrass meadow.…”
Section: Discussionmentioning
confidence: 98%
“…density, stiVness, length, etc.…; see Bouma et al 2005 andKoch andGust 1999 andreferences therein). Hence, we speculate that contrasting results between studies on the growth and/or survival of Wlter feeder in seagrass meadows might perhaps be partly explained by contrasting seagrass canopy properties by having diVerent eVects on food supply.…”
Section: Introductionmentioning
confidence: 99%
“…In these sites, A. zelandica densities are an order of magnitude greater than the densities found in St. Joe Bay; these high densities may be the reason behind the modiWcation of water Xow by pen shells and their inXuence on settling organisms in nearby areas (Norkko et al 2006). The New Zealand sites have water velocities ranging from 0.05 to 0.35 m s ¡1 (Hewitt et al 2002) while in St. Joe Bay water Xows much slower, at 0.027-0.045 m s ¡1 (Koch and Gust 1999), which would also help explain the inXuence of A. zelandica density on the surrounding macrofauna diversity in New Zealand. However, these studies focused on species living in the substrate adjacent to pen shells and not on dead pen shell inhabitants.…”
Section: Discussionmentioning
confidence: 99%
“…This connection between sea grass beds and pen shell communities may be direct (e.g., inhabitants of pen shells directly beneWting from the surrounding sea grass) or indirect (e.g., pen shells and sea grass both beneWting from similar factors such as current and nutrients). St. Joe Bay's T. testudinum meadows can reduce water turbulence (Koch and Gust 1999), which would enhance propagule settlement on to pen shells. One explanation for this variation is that shell density seems to aVect motile but not sessile species community structure.…”
Section: Discussionmentioning
confidence: 99%